Leishmania replication protein A-1 binds in vivo single-stranded telomeric DNA - Siqueira Neto, J. L.; Lira, C. B. B.; Giardini, M. A.; Khater, L.; Perez, A. M.; Peroni, L. A.; dos Reis, J. R. R.; Freitas-Junior, L. H.; Ramos, C. H. I.; Cano, M. I. N. (Elsevier B.V., 2007)
Replication protein A (RPA) is a highly conserved heterotrimeric single-stranded DNA-binding protein involved in different events of DNA metabolism. In yeast, subunits 1 (RPA-1) and 2 (RPA-2) work also as telomerase recruiters and, in humans, the complex unfolds G-quartet structures formed by the 3' G-rich telomeric strand. In most eukaryotes, RPA-1 and RPA-2 bind DNA using multiple OB fold domains. In trypanosomatids, including Leishmania, RPA-1 has a canonical OB fold and a truncated RFA-1 structural domain. In Leishmania amazonensis, RPA-1 alone can form a complex in vitro with the telomeric G-rich strand. In this work, we show that LaRPA-1 is a nuclear protein that associates in vivo with Leishmania telomeres. We mapped the boundaries of the OB fold DNA-binding domain using deletion mutants. Since Leishmania and other trypanosomatids lack homologues of known telomere end binding proteins, our results raise questions about the function of RPA-1 in parasite telomeres. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: replication protein A-1; Leishmania amazonensis; OB fold; telomere end binding protein; immunolocalization